2004
DOI: 10.1007/s11274-003-4514-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of the gene encoding a fibrinolytic enzyme from Bacillus subtilis Strain A1

Abstract: A fibrinolytic metalloprotease gene from Bacillus subtilis has been cloned in Escheridria coli XL1-Blue and the bacterial expressed enzyme was purified. The nucleotide sequence of the cloned fibrinolytic enzyme gene revealed a single open reading frame of 1023 bp coding for 341 amino acids (M r 37708.21 Da). N-terminal amino acid sequencing of the fibrinolytic enzyme excreted from E. coli host cells revealed that the mature fibrinolytic enzyme consists of 288 amino acids (M r 31391.1 Da). The deduced amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 20 publications
1
26
1
Order By: Relevance
“…1 and Table 1). The purified fibrinolytic enzyme was an approximately 28 kDa, which was slightly different from the 31 kDa metalloprotease BK II identified in the same strain (Jeong et al, 2004a). The fibrinolytic activities of the 28 kDa fibrinolytic enzyme, designated as Bacillokinase I (BK I), in the plasminogen-free Polyacrylamide gel electrophoresis of the fibrinolytic enzyme (BK I) purified from B. subtilis strain A1.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…1 and Table 1). The purified fibrinolytic enzyme was an approximately 28 kDa, which was slightly different from the 31 kDa metalloprotease BK II identified in the same strain (Jeong et al, 2004a). The fibrinolytic activities of the 28 kDa fibrinolytic enzyme, designated as Bacillokinase I (BK I), in the plasminogen-free Polyacrylamide gel electrophoresis of the fibrinolytic enzyme (BK I) purified from B. subtilis strain A1.…”
mentioning
confidence: 89%
“…We previously reported a fibrinolytic enzyme (Bacillokinase II, BK II) from B. subtilis strain A1, which is a metalloprotease (Jeong et al, 2004a). In this paper, the fibrinolytic enzyme, which is distinguished from BK II and other known fibrionlytic enzymes with regard to biochemical characteristics, was found and characterized by biochemical and molecular analyses.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…KA38. Jeong et al (2004) reported a fibrinolytic metalloprotease from Bacillus subtilis strain A1, with optimal activity at 50°C. Chiang et al (2005) reported that Wang et al (1999a) Vibrio vulnificus secretes a broad-specific metalloprotease capable of interfering with blood hemostasis.…”
Section: Biochemical Characteristics Of Purified Microbial Fibrinolytmentioning
confidence: 99%
“…have also been interested in the thrombolytic agent because of a high efficiency in the fibrinolytic reactions such as plasmin activation. A variety of extracellular and intracellular proteases including Subtlisin Carsberg [22], nattokinase [19], amylosachariticus [26], aprE [20], Subtilin J [8] and BK II [9] have been produced by the Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%